OP0154 Integrated Safety Analysis of Tofacitinib in RA Clinical Trials with A Cumulative Exposure of 12, 664 Patient-Years. (10th June 2014) - Cohen, S.; Tanaka, Y.; Mariette, X.; Curtis, J.; Kwok, K.; Lee, E.; Nash, P.; Winthrop, K.; Charles-Schoeman, C.; Thirunavukkarasu, K.; Anisfeld, A.; Wang, L.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Phase (P) 2, P3, and open-label long-term extension (LTE) studies described the safety profile of tofacitinib and demonstrated that tofacitinib is effective as monotherapy and in combination with non-biologic disease-modifying antirheumatic drugs (DMARDs). Objectives: This analysis describes safety data for tofacitinib in patients (pts) from the integrated RA clinical trial database based on cumulative exposure in P2, P3, and LTE studies, with a focus on safety events of special interest according to duration of tofacitinib exposure. Methods: The analysis was performed on pts who received ≥1 dose of tofacitinib (doses pooled), as monotherapy or with background DMARDs, integrated across 6 P2, 6 P3 trials, and in 2 LTE studies (ongoing; database not locked) up to April 10, 2013. Pts switching from placebo, adalimumab or methotrexate to tofacitinib contributed data following their first dose of tofacitinib. Incidence rates (IR; events/100 patient-years [py] and 95% confidence intervals [CI]) are listed. The IR for opportunistic infections (OI) included herpes zoster (HZ) events that were described as disseminated or multidermatomal and excluded events of tuberculosis (TB), which are reported separately. Results: The analysis includes 5, 671 pts and represents an overall 12, 664 py of tofacitinib exposure, with a median exposure of 2.4 years. The numbers of pts receiving tofacitinib for at least 12, 24, 36 and >48 months were 4, 204 (74%), 3, 804 (54%), 1, 948 (34%), and 555 (10%) respectively. Overall 926 (16.3%) discontinued due to adverse events (AEs). The IR for mortality (within 30 days of last dose) was 0.28 (0.20, 0.39). IRs across discrete 6-month periods of exposure for serious AEs (SAEs) and AEs of interest, were stable across time intervals (Table 1 ). Serious infections were the most common SAEs (IR 2.93 [2.65, 3.25]). IRs for OI and TB were 0.25 (0.18, 0.36) and 0.21 (0.14, 0.30), respectively. Of all HZ AEs (overall IR 4.22 [3.87, 4.61]), 93% were non-serious; disseminated and multidermatomal cases were rare. Rates of all malignancies, excluding non-melanoma skin cancer (NMSC), and of lymphoma/lymphoproliferative disorders, were similar across time intervals (Table 1 ). US Surveillance, Epidemiology, and End Results Program (SEER) standardised incidence ratios (95% CI) were 1.08 (0.89, 1.31) for malignancies excluding NMSC and 2.58 (1.24, 4.74) for lymphoma, and were comparable to those reported from cohorts of RA pts treated with tumour necrosis factor inhibitors. Conclusions: The pattern and rate of SAEs, and AEs of special interest observed following >12, 000 py of overall exposure was stable across time intervals. No new risks were identified compared to previous reports. Longer term follow-up, observational research, and pharmacovigilance activities will further characterise the safety profile of tofacitinib in RA. Acknowledgements: All studies were sponsored by Pfizer Inc. Editorial support was provided by Claire Cridland, of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: S. Cohen Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, Y. Tanaka Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, X. Mariette Grant/research support: Pfizer Inc, J. Curtis Grant/research support: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Lee Consultant for: Pfizer Inc, P. Nash Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, K. Winthrop Grant/research support: Pfizer Inc, C. Charles-Schoeman Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, K. Thirunavukkarasu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Anisfeld Shareholder of: Pfizer Inc, Consultant for: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Riese Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Wollenhaupt Grant/research support: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.5656